Outcomes of mono-lateral limb reconstruction system in infected non-union of long bones - Gajbhiye, Anuj Induprakash; Goyal, Sidhant; Mohan Kumar, M.; Dorai Kumar, R. (International Journal of Research in Orthopaedics, 2017)
Background: We planned to evaluate functional and radiological outcomes of mono-lateral limb reconstruction system for infected non-union of long bones and to analyse its complications occurring. Methods: It was a prospective study, conducted during period of September 2015 to August 2017 and consisted of 73 cases of these 60 cases were available for final assessment. This infected non-union were classified by AO classification and were treated with mono lateral limb reconstruction system. All the cases were evaluated by ASAMI criteria for bony and functional outcomes. Our mean follow up period was 16.8 months. Results: Among 60 cases of infected non-union with mono-lateral external fixator were followed for mean 16.8 months. According to these ASAMI criteria in our study 26.6% had excellent; 46.6% had good; 16.6% fair; and 10% poor bony outcome. And the functional outcomes were 13.3%, 60%, 16.6%, 10% were excellent, good, fair and poor respectively. Among the cases 50% had pin tract infections and loosening. Two cases pin revision was done. Sinus tract got cleared in all cases except 6 where multiple sinus tracts were present and healing did not occur. There were no infections at the corticotomy site. Delay in the consolidation phase was present in all cases. There was no difficulty in transportation of bone. Post-operatively wound dehiscence in eight cases was managed with split skin graft cover. Limb length discrepancy upto 2.5 cms in lower limb was managed with modified footwear with heel and sole raise. Non-healing fractures united in mean 5.9 months after start of treatment. Non-union site united in 90% cases. Conclusions: Mono-lateral limb reconstruction system is efficient method for treatment of infected non-union of long bones. It has an additional advantage of correcting limb length discrepancies which sometimes occur during the course of treatment. Keywords: Non-union, Infection, Long bones, Limb reconstruction system, External fixator